AN EXAMINATION OF THE COSTS AND OUTCOMES OF EDUCATION IN BOTH PRIVATE AND PUBLIC HIGH SCHOOLS, WITH EMPHASIS ON YARIPORA ZONE IN THE KULGAM DISTRICT - Salahuddin Rather; Aejaz Ahmad Mir (RADJA PUBLIKA, 2023)
ABASTRACTThe present study was intended to explore the analysis of the expenditures of educational institution in both government and private schools.Data on these components were compared between the public private schools in the zone. For each of these elements, indicators were discovered and attributes were created monthly and yearly fee spending, transportation costs, infra-structure and other study-related expenses were studied. The sample for the study was 50 students from different government and private schools of zone yaripora of kulgam district of union territory of Jammu and Kashmir, however, in order to minimise the extraneous effect the researcher has done multi stage random sampling. . A proportionate distribution of students was made, the researcher has used the cross tabulation and percentage methods .Results revealed the outcome from Private institutions is better than Government institutions. Besides the cost of education is very high.The students of Private institutions have better hold on holisticdevelopment. Publicschools having better infrastructure facilities, but public institutions are not providing suitable outcome